2018
DOI: 10.15421/40281019
|View full text |Cite
|
Sign up to set email alerts
|

Взаємозв'язок Між Загальними Та Ефективними Водонепроникними Покриттями Під Час Моделювання Дощового Водовідведення

Abstract: На прикладі житлового кварталу по вул. Широкій у Львові підтверджено важливість поділу загальних водонепроникних покриттів на напряму приєднані до міської каналізаційної мережі (ефективні), водонепроникні покриття та не приєднані водонепроникні покриття. На підставі аналізу та узагальнення результатів дослідження мікрорайонів Денвера (США) (Alley & Veenhuis, 1983) та території Маріон Каунті (США) (Yang et all., 2011) отримано узагальнені степеневі залежності частки ефективних водонепроникних покриттів рeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…As a result of full-scale survey of the territory, the boundaries and types of covers of the quarters were defined. This time-consuming work eliminates errors caused by shading or distortion in satellite images when surveyed using the GIS-based maps (Gironas et al, 2010;Sanzana et al, 2017;Zhuk et al, 2018). During the study, the peculiarities of connection of different sites to the centralized drainage network for each quarter were determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of full-scale survey of the territory, the boundaries and types of covers of the quarters were defined. This time-consuming work eliminates errors caused by shading or distortion in satellite images when surveyed using the GIS-based maps (Gironas et al, 2010;Sanzana et al, 2017;Zhuk et al, 2018). During the study, the peculiarities of connection of different sites to the centralized drainage network for each quarter were determined.…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of impervious surfaces is one of the most important input parameters in the Stormwater modelling. A number of previous studies have shown that an effective or total imperviousness is a more adequate factor characterizing the stormwater runoff entering the sewer system, compared to the total imperviousness (Alley and Veenhuis, 1983;Lee and Heaney, 2003;Zhuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today it is proven that the division of the territory only into pervious and impervious surfaces is too simplistic and gives false values in determining the runoff volume. The detailed description of impervious surfaces and the division of the cover type into effective impervious surfaces and unconnected impervious surfaces changes the value of the total runoff coefficient by 14 % [5]. It is particularly difficult to determine the runoff coefficient from water pervious urban areas (open spaces) since the numerical value of runoff coefficient depends on both the hydraulic parameters of the soil and the hydrological condition of the territory (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…На сьогодні розроблено цілу низку методів, спрямованих на вирішення цієї проблеми. В умовах щільної міської забудови одним з найефективніших методів регулювання дощового стоку є використання водопроникних удосконалених покриттів (ВУП) (Pilon et al, 2019;Tkachuk & Zhuk, 2012;Zhuk et al, 2018).…”
unclassified